Economic integration and labor market institutions : worker mobility, earnings risk, and contract structure - Ronnie Schöb; David E. Wildasin (Institute for the Study of Labor (IZA), 2003)
This paper investigates the effects of labor market integration, in the form of worker mobility, in a model with long-term labor contracts that lead to wage rigidities and unemployment. Reflecting the interdependence of regional labor markets, we develop a general-equilibrium framework where the contract structure is simultaneously determined in all regions. It is shown that increased mobility leads to more flexible labor market institutions in which firms can more easily vary the level of employment in response to fluctuations in demand. Economic integration is potentially Pareto-improving but, in the absence of a system of compensation, workers are harmed by greater labor mobility while the owners of firms benefit from higher profits.
Keywords: J6; R0; J1; 330; migration; unemployment; labor market integration; risk; Arbeitsmarkttheorie; Marktintegration; Internationale Arbeitsmobilität; Lohnverhandlungstheorie; Lohnrigidität; Implizite Kontrakte; Wohlfahrtseffekt; Theorie